Risk among cleaners: The usage of personal protective equipment (PPE) - Nur Syazwani, Mohd Nawi; Ting, Huey Yin; Ezrin Hani, Sukadarin (Global Academic Excellence, Kota Bharu, Kelantan, 2020)
Personal Protective Equipment (PPE) is involved in many industries including cleaning nowadays. The influence factors and usage levels of PPE are very different based on groups. The data in this research is to collect and analysis through the qualitative method. A total of 34 cleaners was observed and interviewed. In this study, the influence factors of PPE usage included the scope of job tasks and works environment, organization culture, rule and enforcement, PPE accessibility/ availability, personal feeling and perspective, knowledge and awareness on safety and hazard factors, and personal behavior. The result also showed that the PPE usage condition is good at a moderate level which fits the cleaning tasks and works environment. The risk of cleaners is low. However, UCLEANSB takes safety action to maintain and enhance the PPE usage among cleaners. For further study, the study can implement to other diverse cleaning group samples with different job task categories.